Konsep dan Karakteristik Borderscapes Migrasi dan Perbatasan di Indonesia: Tantangan dan Peluang - Rusli, Adi Saputra; Saputra, Fahrizal; Saputra, Nur Cholik Widyan; Virginia, Tesalonika; Iswahyudi M, Yanwar (Jurnal Kajian Stratejik Ketahanan Nasional, 2022)
The characteristics of the traditional border concept focuses on geographic and physical aspects. Therefore, the concept of traditional borders focuses on visual appearances such as border walls, demarcation lines, or border stakes and posts. The concept of borderscapes is different from the concept of traditional borders. Borderscapes is defined as an area that is formed and continues to be reshaped by transnational flows that go beyond the modern idea or concept of the national territory. This article discusses various matters related to the concepts, characteristics, and paradigms of border inspection practices, both in general and within the scope of Indonesia's territory. Keywords: Borderscapes, Border Paradigm; Traditional Border, Migration